PERSEPSI MASYARAKAT TERHADAP PENYIARAN DAKWAH ISLAMIYAH MELALUI TELEVISI SWASTA DI KOTA BANJARMASIN - Supriyadi Hadi Saputra (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2017)
This research is a field research which is sampling study. The sample is taken from by using porpusive sampling technique as many as 50 people with sample distribution as many as 10 people from 5 districts in Banjarmasin. Data collection technique is done by conducting interviews to the respondents, which then analysis is done qualitatively. From the results of the study note that from 50 respondents who are the authors carefully, then their perceptions can be categorized in two groups of opinions. The first group consists of 38 respondents who argue that broadcasting Islamic da'wah through private television in the city of Banjarmasin is a new pattern in Islamic da'wah. Because most da'wah in the past done only by using simple media, ie through direct meeting or assembly taklim. So someone who wants to follow an Islamic da'wah activities should come to the place of da'wah. This second group consists of 12 respondents who argue that broadcasting Islamic da'wah through private television in Banjarmasin City is a new pattern in da'wah Islamiyah, in the local context. But not enough, and need to be upgraded in the packaging or form of lecture, which is more compressed on the interactive form. The reason of the first group that the da'wah through media tekevisi broadcast by private television in the city of Banjarmasin, shows dakwah in Banjarmasin is a significant increase. According to this first group, private television programs broadcasting propagation programs such as TV Ambassador and Banjar TV are good enough, because the material of dakwah is quite varied, such as ketauhidan, Islamic law, and morals. Then there is also a commentary of the hadith of the Prophet Muhammad SAW. but according to this second group, the da'wah broadcast by private television in Banjarmasin city is good enough, but still need to be improved again its dakwah program. Like more interactive dialogue compared to da'wah in the form of non-interactive religious lectures.